DETECTIN OF VASPIN RS2236242 AND CHEMERIN RS17173608 GENE POLYMORPHSIMS IN A SAMPLE OF OBESE IRAQI POLYCYCTIC OVARY SYNDROME WOMEN - & et al., Jasim (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was performed to detect assess Vaspin rs2236242 and Chemerin rs17173608 gene polymorphisms with its association with susceptibility of obese PCOS in Iraqi women .Blood samples from 100 women with obese PCOS and 75 healthy control women matched in age and BMI were collected from AL-Yarmouk Teaching hospital during February2018-July 2018 were enrolled in case control study. Tetra amplification refractory mutation system‐polymerase chain reaction (T-ARMS-PCR) was performed to detect the adipokine SNPs in patients and healthy women under study. Results demonstrated a significant variations in either genotype distribution and alleles frequencies between the obese PCOS and healthy women regarding vaspin rs2236242 polymorphism. The T allele increased the PCOS risk in comparison with the A allele which was the protective against PCOS, as well clear positive correlation between rs17173608 SNP of chemerin and susceptibility of PCOS was identified also, and The T allele had related with elevated PCOS risk as in comparison to the G allele. Data from this work determined for the first time a significant association between vaspin and chemerin SNPs and susceptibility PCOS risk in Iraqi obese women especially T allele .To confirm our findings new studies with large sample size and different ethnicities must be required.